2009
DOI: 10.1111/j.1551-2916.2009.03046.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Compound with Ultra Low Dielectric Loss at Microwave Frequencies

Abstract: A new ultra low loss microwave dielectric ceramic, Mg(Sn0.05Ti0.95)O3 (MSnT), was found and investigated. The compounds were prepared by the conventional solid‐state route, and sintered at 1360°–1480°C for 2–6 h. The investigations show that the MgTi2O5 secondary phase was observed. Moreover, the dielectric properties were correlated with the formation second phase. The excellent microwave dielectric properties of Q×f=322 000 (GHz), ɛr=17.4, and τf=−54 ppm/°C were obtained from the new MSnT ceramics sintered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The grain morphology exhibits two different types of grains: circular grains and rod-shaped grains. A similar result was observed by Tseng [17], who suggested that the circular grains might be ilmenite phase and the rod-shaped grains could be Mg 0.95 Ni 0.05 Ti 2 O 5 phase. The semi-quantitative SEM EDS (Table 1) of the grains labeled as "A" and "B" indicated that the composition of these grains was close to Mg 0.95 Ni 0.05 Ti 0.98 Zr 0.02 O 3 and Mg 0.95 Ni 0.05 Ti 2 O 5 , respectively.…”
Section: Methodssupporting
confidence: 81%
“…The grain morphology exhibits two different types of grains: circular grains and rod-shaped grains. A similar result was observed by Tseng [17], who suggested that the circular grains might be ilmenite phase and the rod-shaped grains could be Mg 0.95 Ni 0.05 Ti 2 O 5 phase. The semi-quantitative SEM EDS (Table 1) of the grains labeled as "A" and "B" indicated that the composition of these grains was close to Mg 0.95 Ni 0.05 Ti 0.98 Zr 0.02 O 3 and Mg 0.95 Ni 0.05 Ti 2 O 5 , respectively.…”
Section: Methodssupporting
confidence: 81%
“…: +886 37 381529; fax: +886 37 362809. E-mail address: cftseng@nuu.edu.tw site of the MgTiO 3 ceramics was not reported in the literature until the work of Tseng and coworkers [6,7]. It has been well documented that a small amount of impurity ion substitution can dramatically modify the microwave dielectric properties of MgTiO 3 ceramics; however, the dielectric properties of substitution of M 4+ at the Bsite in MgTiO 3 is better than those of the substitution of M 2+ at the A-site.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, no significant change was observed for specimens sintered at temperatures 1310-1430 • C. The lattice parameters was measured for Mg 1 microstructure was developed with numbers of pores and the grain size of the specimen was small, with an average grain size 2.27 m. The increase of sintering temperature helped to promote the grain growth and a relative increase in the grain size was achieved for specimen sintered at 1370 • C. It was not until the temperature reached 1430 • C, that a rapid grain growth started to appear due to the over-sintering of the specimens and the grains are of relatively large size to an average of 29.11 m. The grain size distributions are not very uneven compared to that prepared by a chemical route. However, a relatively uniform microstructure with low porosity was obtained for specimen sintered at 1400 • C. The well-developed microstructure has an average grain size of 27.27 m, which is larger than that of stoichiometric MgTiO 3 ceramics [20] further confirming the promoted grain growth is due to the excess Mg content. Notice that the grain size analysis was accomplished by using the ASTM (American Society for Testing Material) E112 standard rules.…”
Section: Resultsmentioning
confidence: 63%